2016
DOI: 10.1177/8756479316669677
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of Perihepatic Abscess From Dropped Appendicolith

Abstract: Appendicitis is a common pathology most often caused by an appendicolith. Laparoscopic appendectomy has become the standard operative approach, but it has a higher risk of retained appendicoliths than open laparotomies. This report describes a case of a perihepatic abscess due to a retained appendicolith following laparoscopic intervention. The abscess was successfully drained and the appendicolith retrieved percutaneously under fluoroscopic guidance. A literature review and discussion about retained appendico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The timeline for developing an infection or an abscess varies and has been reported after a few months to up to 7 years as in our case 6. Thus it should be considered as a differential for an intra-abdominal abscess in an appropriate clinical setting even if the patient has a remote history of appendicectomy 2…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The timeline for developing an infection or an abscess varies and has been reported after a few months to up to 7 years as in our case 6. Thus it should be considered as a differential for an intra-abdominal abscess in an appropriate clinical setting even if the patient has a remote history of appendicectomy 2…”
Section: Discussionmentioning
confidence: 68%
“…A retained appendicolith may result if the appendicolith is missed intraoperatively or if there is a ruptured appendix and the appendicolith is displaced into the abdominal cavity. As compared with gallstones that are mostly sterile, appendicoliths are not sterile and are a high risk to act as a nidus for infection or abscess formation 2. They are most commonly located in the paracaecal region, but have been reported to occur elsewhere too, and have been reported in the pouch of Douglas, retrovesical pouch, fallopian tubes, iliopsoas and the gluteal region and perihepatically 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perihepatic abscesses resulting from dropped appendicoliths are uncommon and a review of the literature has revealed 11 cases in 10 reports, including the present one ( Table 1 ) [ [6] , [7] , [8] , [9] , 11 , [15] , [16] , [17] , [18] ]. All 11 patients had appendicectomy for perforated appendicitis and presumably, the dropped appendicoliths were secondary to the perforation.…”
Section: Discussionmentioning
confidence: 87%
“…One patient was successfully managed with antibiotics without drainage of the abscess [17] , but this is the exception rather than the rule. Two patients had successful percutaneous drainage of the abscess with subsequent (up to several weeks later) percutaneous extraction of the appendicolith [7 , 18] . One patient had successful percutaneous drainage of the abscess without retrieval of the appendicolith [11] and two had percutaneous drainage of the abscess with subsequent surgical retrieval of the appendicolith [11 , 15] .…”
Section: Discussionmentioning
confidence: 99%